LINGUOPOETIC CHARACTERISTICS OF ONOMASTIC UNITS IN KASHKADARYA FOLK EPISTLES - Abatov Doston (The American Journal of Social Science and Education Innovations, 2023)
This article is dedicated to highlighting the linguopoetic features of onomastic units used in the text of Kashkadarya folk epics, nouns in the epics form the text as an alleutic unit in addition to the nominative function and provide intertextuality, create a comic effect, and express a negative or positive assessment, it is proved by examples from folklore works that it fulfills the functions of expressing strong emotions, clarifying the image as part of a rhetorical figure, and expressing appeals with different meanings.